Contraceptive Use and Intent in Guatemala - Kathryn Grace (Demographic Research, 2010)
Guatemala is characterized by low contraceptive use rates and one of the highest fertility rates in the Western Hemisphere. These rates are particularly extreme for the poorest segment of the population and for the indigenous population. The purpose of this research is to enhance understanding of the modern contraceptive revolution in Guatemala through identification of the segments of the Guatemalan population at most need for contraceptive and family planning services. Using the most recently available survey data, the 2002 Reproductive Health Survey data set (RHS), classification trees will be used to determine the women with greatest need for reproductive health services. The results highlight the persistent marginalization of the poor and the indigenous and provide further insight into the impact of education, place of residence and couple characteristics on contraceptive use and intent.